Effects of Chlorhexidine and normal saline on dental plaque formation in ICU patients: A comparative study - Jafari, S; Ranjbar, H; Kamrani, F; Alavi- Majd, H; Yaghmaei, F (Advances in Nursing & Midwifery, 2007)
Abstract Introduction: The mechanism of respiratory infections is the colonization of aero-digestive tract and the subsequent aspiration of contaminated secretion into the lower part of respiratory tract. In the first 48 hours of admission, the normal oropharyngeal flora change to anaerobic gram negative bacilli and the dental plaques are suitable environments for growth of pathogens. Purpose: This randomized clinical trial was conducted to compare the effects of chlorhexidine with normal-saline mouthwashes on dental plaque formation in ICU patients under mechanical ventilation. Materials and Methods: 80 patients with endotracheal tube were randomly divided into two equal control and experimental groups. The experimental and control groups received chlorhexidine %0.2 and normal saline mouthwashes twice a day with tooth and mouth swabs. Plaque index was calculated over 3 days. Results: The total incidence of the pneumonia was 27.5%. the incidence rate in experimental and control groups were 22.5% and 32.5% respectively with no significant difference (CL=95%0.439-1.336, RR= 0.765 , P= 0.453). Also there was no significant correlation between pneumonia incidence and variables of sex, internal or surgical conditions and history of antibiotic therapy but a correlation was found with severity of disease (p= 0.00). Conclusion: Findings showed difference between twice-a–day oral decontamination with Chlorhexidine 0.2% and normal saline solution in prevention of ventilator pneumonia. This was probably as a result of physical effects of oral rinse. Key words: Mouth rinse, Chlorhexidine, Normal saline, Dental plaque.